MINIMALISTIC WEB UI: A STRUCTURED PARADIGM FOR CONTENT-CENTRIC INTERFACE DESIGN AND INTUITIVE USER NAVIGATION - Лукашук, Микола; Зозуля, Юлія (SWorldJournal, 2025)
The article proposes a methodology for creating a web interface design aimed at improving readability, reducing cognitive load, and ensuring intuitive user interaction with digital platforms. The purpose of the work is to develop an approach that provides